Cost-effectiveness of IMI/CIL/REL for the treatment of carbapenem non-susceptible Gram-negative bacterial infections - Martina Paoletti; Andrea Marcellusi; Joe Yang; Francesco Saverio Mennini (Global & Regional Health Technology Assessment, 2023)
Objective: The objective of this analysis was to evaluate the cost-effectiveness of imipenem/cilastatin/relebactam compared to colistin-imipenem in the treatment of hospitalized patients with Gram-negative bacterial infections caused by imipenem-resistant pathogens. The perspective was both that of the National Health Service (NHS) and the social one.